Discovery of an inhibitor of the production of the Pseudomonas aeruginosa virulence factor pyocyanin in wild-type cells - Morkunas, Bernardas; Gal, Balint; Galloway, Warren R. J. D.; Hodgkinson, James T.; Ibbeson, Brett M.; Sing Tan, Yaw; Welch, Martin; Spring, David R. (Beilstein Journal of Organic Chemistry, 2016)
Pyocyanin is a small molecule produced by Pseudomonas aeruginosa that plays a crucial role in the pathogenesis of infections by this notorious opportunistic pathogen. The inhibition of pyocyanin production has been identified as an attractive antivirulence strategy for the treatment of P. aeruginosa infections. Herein, we report the discovery of an inhibitor of pyocyanin production in cultures of wild-type P. aeruginosa which is based around a 4-alkylquinolin-2(1H)-one scaffold. To the best of our knowledge, this is the first reported example of pyocyanin inhibition by a compound based around this molecular framework. The compound may therefore be representative of a new structural sub-class of pyocyanin inhibitors, which could potentially be exploited in in a therapeutic context for the development of critically needed new antipseudomonal agents. In this context, the use of wild-type cells in this study is notable, since the data obtained are of direct relevance to native situations. The compound could also be of value in better elucidating the role of pyocyanin in P. aeruginosa infections. Evidence suggests that the active compound reduces the level of pyocyanin production by inhibiting the cell–cell signalling mechanism known as quorum sensing. This could have interesting implications; quorum sensing regulates a range of additional elements associated with the pathogenicity of P. aeruginosa and there is a wide range of other potential applications where the inhibition of quorum sensing is desirable.
Keywords: antibacterial; antivirulence; Pseudomonas aeruginosa; pyocyanin; quorum sensing